Faktor-Faktor yang Mempengaruhi Turnover Intention Karyawan Operator Produksi di Perusahaan Garmen - Betsliafra Efata Radsta Yoeti; Wahyuningsih, Tri Harsini (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2026)
This study aims to analyze the factors influencing the intention to quit among production operators in a garment company. Work-family conflict, workload, and leadership are factors considered to influence the intention to quit. The busyness of this department is the main reason for management’s limitation on the number of respondents. Therefore, methodologically, the sample was taken using a non-probability sampling method with a quota sampling technique. Company management only permitted the distribution of questionnaires to a maximum of 100 respondents. After the questionnaires were distributed, 96 questionnaires were available for use in this study. Validity tests showed that all research questions were valid. All researh variables were declared reliable and the data obtained were normally distributed. The results of the classical assumption test found no multicollinearity and no symptoms of heteroscedasticity. The t-test results showed that work-family conflict had a positive effect on intention to quit, with a significance 0f 0.000 and a regression coefficient of 0.456. workload and leadership did not affect intention to quit, with significances of 0.742 and 0.746 respectively. This finding shows that the intention to quit the work of production operator employees is only influenced by the existence of conflict between work and family.